Pengembangan Media Pembelajaran Interaktif Berbasis Powerpoint pada Pembelajaran Bahasa Indonesia di MI Salafiyah 1 Kauman - I’anatul Ashriyah; M. Ali Ghufron (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to develop interactive learning media based on PowerPoint in Indonesian language learning at MI Salafiyah 1 Kauman. The background of this study is the lack of interactive and interesting learning media in elementary schools, especially in Indonesian language subjects. This study uses the Research and Development (R&D) method with the development of the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The media developed contains learning materials, animations, practice questions, and automatic feedback to increase student participation and understanding. The results of the validation test by media experts and material experts show that this media is very suitable for use in learning. Limited trials conducted on students showed an increase in interest, active involvement, and student learning outcomes after using the media. In addition, students feel more motivated and find it easier to understand the material because of the attractive and interactive visual display. Thus, this interactive learning media based on PowerPoint can be an alternative to support a more interesting, enjoyable, and effective learning process in the classroom, especially for elementary school level.